Analysis of platelet transfusion efficacy during extracorporeal membrane oxygenation (ECMO) treatment in pediatric patients post-cardiac surgery-a retrospective cohort study - Chen, Xusheng; Yang, Yongtao (Laboratory medicine, 2025)
Postoperative extracorporeal membrane oxygenation (ECMO) may be necessary for pediatric patients following cardiac surgery, with associated risks of thrombocytopenia and bleeding. Prophylactic platelet transfusions are utilized to mitigate these risks, but the effectiveness of platelet transfusion cannot be reliably predicted. The aim of this study was to investigate the effect of platelet transfusion during postoperative treatment with ECMO in children undergoing cardiac surgery and to explore the optimal transfusion thresholds to reduce the number of platelet transfusions in patients and reduce the risk of death. We included in our study patients from the Pediatric Cardiac Surgery Department at the First Affiliated Hospital of Tsinghua University who underwent cardiac surgery and received ECMO treatment from January 1, 2019, to December 31, 2023, and received platelets transfusion at least once during the ECMO therapy. The platelet counts were determined both before and 24 hours posttransfusion of the platelet product. The corrected count increment (CCI) was calculated for the effectiveness estimation of platelet transfusion. The research subjects were divided into 3 groups based on the platelet count before transfusion (pretransfusion platelet count ≤30×109/L was the low-threshold group, pretransfusion count 31-50×109/L was the medium-threshold group, and ≥51×109/L was the high-threshold group) and the effective rates of each group were calculated. A total of 11 patients received 47 platelet transfusions, an average of 4.27 ± 1.67 per patient. According to the 24-hour postinfusion platelet (Plt) corrected critical control increase index (24-hour CCI) ≥4500, the infusion was considered to be effective, and ineffective when the CCI was <4500. Out of these, 22 transfusions (46.8%) proved effective, whereas 25 (53.2%) were deemed ineffective. The effective transfusion rates across the 3 groups were 69.2%, 50%, and 27.7%, respectively. The efficacy of platelet transfusion may be higher if a low threshold of platelet transfusion is chosen during ECMO treatment, on the premise of ensuring life safety.